2014
DOI: 10.1155/2014/578103
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Antiurolithiatic Activity of Viburnum opulus L. on Sodium Oxalate‐Induced Urolithiasis Rat Model

Abstract: The aim of the present research is to evaluate the antiurolithiatic effect of the various extracts prepared from the fruits of Viburnum opulus L., in regard to its ethnobotanical record. To induce urolithiasis, 70 mg/kg sodium oxalate was injected to the rats which were housed individually in metabolic cages. The test materials were applied during 7 days. Biochemical (urine and serum parameters), histopathological and antioxidant (TBARs, TSH and GSH) assays were conducted. The urine samples were examined by li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 22 publications
4
26
1
1
Order By: Relevance
“…In line with our findings, a report of an experimental model has shown the beneficial effect of V. opulus treatment on the levels of total thiols and glutathione [30] . MDA elevation shows increased lipid peroxidation due to the interaction between lipid components of cellular membranes and ROS [31] .…”
Section: Discussionsupporting
confidence: 93%
“…In line with our findings, a report of an experimental model has shown the beneficial effect of V. opulus treatment on the levels of total thiols and glutathione [30] . MDA elevation shows increased lipid peroxidation due to the interaction between lipid components of cellular membranes and ROS [31] .…”
Section: Discussionsupporting
confidence: 93%
“…Phenolic compounds may prevent the lipid peroxidation-induced renal damage caused by CaOx crystal deposition in the kidney. It was also reported that hypoglccemic, antihyperlipidemic, anti-inflammatory, and antioxidant activities of chlorogenic acid may improve the renal function in diabetic nephropathy [42]. Recent studies have shown that the flavonoids could effectively inhibit the formation of CaOx stones in vitro and in vivo, correlating with their diuretic, antioxidant, anti-inflammatory, antibacterial properties and other protective effects [43].…”
Section: Discussionmentioning
confidence: 98%
“…[16] It has been shown in preclinical studies that this plant, which grows widely in Central Anatolia, has antioxidant, antiurolithiatic, antispasmodic, anti-inflammatory, and antinociceptive effects. [17,18] The aim of the present study was to analyze the efficacy of V. opulus, an alternative herbal treatment method, in distal ureteral stones <10 mm. To the best of our knowledge, this is the first clinical trial evaluating the efficacy of V. opulus in the treatment of ureteral stones.…”
Section: Introductionmentioning
confidence: 99%